Oil in the sea : inputs, fates and effects (National Academy Press, 1985)
Deals with two potentially opposing aspects of man's activities regarding petroleum pollution in the ocean: pollution arising from man's needs for petroleum and a desire to preserve living marine resources.
Updates: Petroleum in the marine environment / Workshop on Inputs, Fates, and the Effects of Petroleum in the Marine Environment. Washington : National Academy of Sciences, 1975.
Keywords: Oil spills -- Environmental aspects.; Oil pollution of the sea.; Oil spills.; Marine pollution.; Pollution marine par les hydrocarbures.; Déversements de pétrole.; Pollution marine.; Déversements de pétrole -- Aspect de l'environnement.; marine pollution.; TECHNOLOGY & ENGINEERING -- Environmental -- Pollution Control.; Oil spills; Marine pollution; Oil pollution of the sea; Oil spills -- Environmental aspects